Enhancing Soil Carbon in East Africa: The biophysical evidence, socio-economic incentives, and policy implications - Nyawira, Sylvia S.; Jernbery, April; Jallo, Courtney; Mayzelle, Megan; Piikki, Kristin; Söderström, Mats; Abera, Wuletawu; Abegaz, Assefa; Ma, Jianyong; Korir, Mercy Jebet; Zerihun, Chere; Karanja Ng'ang'a, Stanley; et al. (2021)
This report provides a summary/sythesis of key research outputs and messages gathered from the four year BMZ-funded project on "Scaling up soil carbon enhancement interventions for food security and climate across complex landscapes in Kenya and Ethiopia."